Spiral arms in CALIFA galaxies traced by non-circular velocities, abundances, and extinctions - Sakhibov, Firuz; Zinchenko, Igor A.; Pilyugin, Leonid S.; Grebel, Eva K.; Just, Andreas (Arxiv, 2017)
We derive maps of the observed velocity of ionized gas, the oxygen abundance, and the extinction (Balmer decrement) across the area of the four spiral galaxies NGC36, NGC180, NGC6063, and NGC7653 from integral field spectroscopy obtained by the Calar Alto Legacy Integral Field Area (CALIFA) survey. We searched for spiral arms through Fourier analysis of the spatial distribution of three tracers (non-circular motion, enhancement of the oxygen abundance, and of the extinction) in the discs of our target galaxies. The spiral arms (two-armed logarithmic spirals in the deprojected map) are shown in each target galaxy for each tracer considered. The pitch angles of the spiral arms in a given galaxy obtained with the three different tracers are close to each other. The enhancement of the oxygen abundance in the spiral arms as compared to the abundance in the interarm regions at a given galactocentric distance is small; within a few per cent. We identified a metallicity gradient in our target galaxies. Both barred galaxies in our sample show flatter gradients than the two galaxies without bars. Galactic inclination, position angle of the major axis, and the rotation curve were also obtained for each target galaxy using the Fourier analysis of the two-dimensional velocity map.